2015
DOI: 10.1002/ardp.201500179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of a Series of Oleanolic Acid Saponins as α‐Glucosidase and α‐Amylase Inhibitors

Abstract: Sixteen naturally occurring oleanolic acid saponins and their derivatives were synthesized in an efficient and practical strategy, and their inhibitory activities against α-glucosidase and α-amylase were evaluated in vitro. Among all the compounds, 28-O-monoglucoside 8 exhibited remarkably potent inhibitory activity against α-glucosidase with an IC50 value of 87.3 µM, which was fivefold stronger than that of the antidiabetic acarbose. Based on the preliminary structure-activity relationships, for 28-O-monogluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…Saponins are triterpene glycosidesbased structures, which are widely distributed in the plant as an active foamy agent. The glycone structures of saponins, especially 28-O-monosides and 3,28-O-bidesmosides, were reported to be contributed to the inhibition of α-glucosidase activity [18]. However, our study showed that a high amount of saponins were less correlated to the inhibition of the α-glucosidase enzyme.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Saponins are triterpene glycosidesbased structures, which are widely distributed in the plant as an active foamy agent. The glycone structures of saponins, especially 28-O-monosides and 3,28-O-bidesmosides, were reported to be contributed to the inhibition of α-glucosidase activity [18]. However, our study showed that a high amount of saponins were less correlated to the inhibition of the α-glucosidase enzyme.…”
Section: Discussioncontrasting
confidence: 67%
“…The plants or natural products contain several active compounds against postprandial hyperglycemia [16]. Plant polyphenols (e.g., flavonoids, xanthones, tannic acids) can exhibit the anti-α-amylase and anti-α-glucosidase enzymes, which result in a reduction of the postprandial hyperglycemia [10,11,[17][18][19][20]. Traditional Thai medicines (TTM) have long been used over decades for the treatment of diabetes mellitus [21].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any previous studies on α-glucosidase inhibition by chrysanthellin B. However, the effects of other molecules from the same sub-families (saponins based on oleanolic acid or oleanane) on this enzyme have been studied and the reported IC 50 values were close to those of acarbose [ 43 , 44 ]. In addition, chlorogenic acid, luteolin, oleuropein, chrysanthellin B, and piperine are precursors or derivatives of several other compounds identified in TOTUM-63 (see Table 2 ) that could also potentially contribute to α-glucosidase inhibition.…”
Section: Discussionmentioning
confidence: 82%
“…This result is consistent with the results reported by Bai and co-workers. 41 The sugar moiety at 4″-OH has a marginal contribution to the activity because protodioscin 4, pallidifloside I 5, coreajaponins A 6, and parisaponin I 7 could similarly inhibit α-glucosidase. To the best of our knowledge, this is the first report on the inhibitory activity of furostanol saponins against α-glucosidase, and…”
Section: Resultsmentioning
confidence: 99%